Makna Mitos Pada Karakter Hewan Dalam Film Mononoke Hime - Anindita, Rizka; Triasih Rahayu, Ely; Puspitasari, Diana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 1 (2022), 2022)
The objective of this study was to describe the meaning contained in the animal characters in the Mononoke Hime movie and then correlated it to Japanese folklore. Type of this study was descriptive qualitative. The data collection technique used was the note taking technique. The researcher watched the Mononoke Hime movie and recorded dialogues related to the study theme. The data analysis technique was conducted by analyzing the dialogues in the Mononoke Hime movie related to the meaning of animals based on Ronald Barthes' semiotic concept. The results of this study showed that there were 4 animal characters that contained mythical meanings based on the analysis of the Mononoke Hime movie and the Youkai reference book. The results of this study showed 4 animals found in the data source, namely deer, wolf, boar and monkey. Each animal had the following characters; The God of deer had the meaning of regulator of living things’s lives in the forest, the god of wolf and the god of boar had the meaning of protecting the forest, and the god of monkey had the meaning of fertility by caring for the god of deer’s forest.